Verteporfin protects against Th17 cell‐mediated EAE independently of YAP inhibition. Issue 9 (25th July 2022) - Brosinsky, Paulin; Leister, Hanna; Cheng, Nan; Varelas, Xaralabos; Visekruna, Alexander; Luu, Maik
Abstract : The known YAP inhibitor verteporfin is capable of repressing IL‐17A production in Th17 cells. However, this effect is mediated independently of YAP and can ameliorate Th17‐mediated experimental autoimmune encephalomyelitis (EAE) upon in vivo administration. The data suggest verteprofin's mode of action for the design of novel therapeutic autoimmune disease intervention.